Implementing Good Governance Using Complied Archive Records Management Systems (ARMS): A Case Study of Faculty of Information Management / Alwi Mohd Yunus ... [et al.] - Mohd Yunus, Alwi; Nik Ariffin, Nik Azliza; Tengku Hisham, Tengku Nisa Zahirah; Zulkipli, Fatin Nur; Mostakim, Muhammad Syawal (Universiti Teknologi MARA, Selangor, 2020)
Technology has brought society to the next level where most organizations started to transact using e-commerce platform and inevitably creating more digital records as output of those transactions. Digital records become primary concern in organiszation as it exists in accelerated volumes thus requiring organizations to manage it right from the point of creation. Failure which would hamper efficient operations of organization. Notably, a proper system is required to manage it, together with its proper standards and policies for successful implementation. The adoption of ICTs in managing records has often been haphazard condition for organizations and management. Such impacts are also felt by government organizations and agencies. Though using ICTs in managing the digital or electronic records, which is the right move by the government as part of modernization process, due to management of digital records or information is a necessary enabler for sustainable business change and to meet proper information policy and compliance requirements based on standard in information governance. However, the solution to all information management problems could not only depend on information and communication technology progress. Good record-keeping could lead to good governance to promote values that are important in gaining and retaining people's trust. Secure information delivery, accountability, transparency in transactions are crucial recordkeeping's element that contribute to people's trust. Therefore, this article is presented in am manner on how Archive Records Management System (ARMS), a digital records management software could help organizations to perform while maintaining accountability through good practices of information and records governance